Informacijos vertinimas - Simanaukas, Leonas (Information & Media, 1997)
The evolution of information meaning and measurement are discussed. The statistical, organizational and economical aspects of information theory are reviewed. The evaluation of information is reviewed from perspective of managers. Relationships bet ween the information as product of management information systems and its end-users processes effectiveness are analysed. The information cost are offered to define from the point of view of managers as cost of resources, used for the producting or services processes management and its effectivity.
Keywords: -